The CCAFS Regional Scenarios Programme: External evaluation report on progress towards programme outcomes - Carey, C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
External evaluation of the CCAFS Scenarios Programme which was initiated in 2010 and is active across all five regions in which CCAFS is engaged, namely South Asia, East Africa, West Africa, Latin America, and South-East Asia. The evaluation concludes that "the CCAFS Scenarios Program is a well developed tool kit that meets all the criteria for achieving its demanding targets. The issues it faces are common to all engagement led projects in that you cannot force people to utilize or even engage with scenarios products, nor can you completely manage those that do involve themselves with the process. However, the signs are very positive that this will happen."